2016
DOI: 10.1007/s00167-016-4273-0
|View full text |Cite
|
Sign up to set email alerts
|

Better functional outcome after single-radius TKA compared with multi-radius TKA

Abstract: Therapeutic study, Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…Though the current study lacks a multi-radius control group, single and multi-radius TKAs have been compared previously. Randomised control trials comparing the Triathlon single-radius TKA with multi-radius TKAs have found in favour of the single-radius design [9, 20, 22]. Hamilton et al [22] reported significantly greater range of motion, more rapid recovery to 116% of quadriceps function compared to the contralateral side, greater satisfaction and reduced ‘worst daily pain’ following Triathlon ( n  = 104) compared to a multi-radius TKA ( n  = 108) over the 3 years of follow-up [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the current study lacks a multi-radius control group, single and multi-radius TKAs have been compared previously. Randomised control trials comparing the Triathlon single-radius TKA with multi-radius TKAs have found in favour of the single-radius design [9, 20, 22]. Hamilton et al [22] reported significantly greater range of motion, more rapid recovery to 116% of quadriceps function compared to the contralateral side, greater satisfaction and reduced ‘worst daily pain’ following Triathlon ( n  = 104) compared to a multi-radius TKA ( n  = 108) over the 3 years of follow-up [22].…”
Section: Discussionmentioning
confidence: 99%
“…Hamilton et al [22] reported significantly greater range of motion, more rapid recovery to 116% of quadriceps function compared to the contralateral side, greater satisfaction and reduced ‘worst daily pain’ following Triathlon ( n  = 104) compared to a multi-radius TKA ( n  = 108) over the 3 years of follow-up [22]. Collados-Maestre et al [9] found significantly better knee society scores, WOMAC pain scores, range of motion and quadriceps strength in the single-radius group when comparing 118 single-radius and 119 multi-radius TKA designs at 5–7 years [9]. Biomechanical studies comparing single and multi-radius TKAs have found larger amounts of axial rotation in single-radius knees using dynamic fluoroscopy [19] and better power absorption during weight acceptance in single-radius TKAs at gait analysis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Palmer et al [22] compared 388 cases of SR and 674 cases of MR, and they found a significantly better flexion and KSSs in the SR group upon either 1-or 2-year follow-up than in the MR group, and 66.3% of their patients didn't experience any pain after 2 years against 54.4% of the patients with MR knees. Collados-Maestre et al [18] conducted the largest-sized RCT comparing the clinical outcomes and reported significant better KSSs, ROM, extension lag, quadriceps strength, chair test, and WOMAC pain and a higher satisfaction rate in the SR group. In our study, there were no significant differences in KSS-knee, function score and all the aspects of KOOS score, which is coincident with the previously reported findings [15,18,22].…”
Section: Discussionmentioning
confidence: 99%
“…In a cadaveric study, the SR knee required 57% less quadriceps force as compared to the MR knee, and the author inferred that SR design could reserve the strength of the extensor mechanism substantially [24]. Collados-Maestre et al [18] reported that the SR group showed a significantly better quadriceps strength than the MR group. Mahoney et al [8] found that 90% of the patients in the SR group, which was significantly higher than the proportion in the MR group, could rise from a folded chair independently at 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation